2017
DOI: 10.1101/gad.292318.116
|View full text |Cite
|
Sign up to set email alerts
|

miR-424(322)/503 is a breast cancer tumor suppressor whose loss promotes resistance to chemotherapy

Abstract: The female mammary gland is a very dynamic organ that undergoes continuous tissue remodeling during adulthood. Although it is well established that the number of menstrual cycles and pregnancy (in this case transiently) increase the risk of breast cancer, the reasons are unclear. Growing clinical and experimental evidence indicates that improper involution plays a role in the development of this malignancy. Recently, we described the miR-424(322)/503 cluster as an important regulator of mammary epithelial invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(57 citation statements)
references
References 85 publications
1
55
1
Order By: Relevance
“…It is possible that miR-424 regulates other aspects besides the effects on HPV genome amplification via modulation of the ATR DNA damage pathway. Recent studies have shown that miR-424 also regulates BCL-2 and insulin-like growth factor 1, suggesting that it has tumor suppressor activities (33). In contrast to our observations with HPV, the levels of miR-424 are increased in EBV-positive, diffuse, large B cell lymphomas (34).…”
Section: Discussioncontrasting
confidence: 72%
“…It is possible that miR-424 regulates other aspects besides the effects on HPV genome amplification via modulation of the ATR DNA damage pathway. Recent studies have shown that miR-424 also regulates BCL-2 and insulin-like growth factor 1, suggesting that it has tumor suppressor activities (33). In contrast to our observations with HPV, the levels of miR-424 are increased in EBV-positive, diffuse, large B cell lymphomas (34).…”
Section: Discussioncontrasting
confidence: 72%
“…Loss of miR-424 was associated with aggressiveness of breast cancers in human. Knockout of miR-424 promoted breast tumorigenesis in mice [40]. miR-4286 was also highly expressed in chemosensitive tumors [16].…”
Section: Circrnaome Of Ebv Sponged Mirnas Of Host Cells Involved In Mmentioning
confidence: 99%
“…Nakashima et al [32] demonstrated a regulatory mechanism of angiogenesis in the aged skin from miRNAs, in particular showing that a decreased mir-424 expression and increased levels of MEK1 (mitogen-activated protein kinase) or cyclin E1 may cause abnormal cell proliferation. It has also been reported that microRNAs play an important role in the case of breast cancer, and in particular the loss of miR-424(322)/503 was associated with poor prognosis characteristics such as a high-grade tumours, a larger pathological tumour size, a triple-negative status, and strong cell proliferation ( KI67 mRNA expression) [33]. These observations leave at least the doubt that cytokine produced by cancer cells can determine the common dysfunction of microRNAs.…”
Section: Discussionmentioning
confidence: 99%